2021
DOI: 10.1111/hex.13264
|View full text |Cite
|
Sign up to set email alerts
|

Advance care directive prevalence among older Australians and associations with person‐level predictors and quality indicators

Abstract: Background Advance care planning (ACP) conversations may result in preferences for medical care being documented. Objective To explore the uptake and quality of advance care directives (ACDs) among older Australians accessing health and aged care services, by overall ACP documentation prevalence, person‐level predictors and ACD quality indicators. Design and Setting National multi‐centre health record audit in general practices (GP), hospitals and residential aged care facilities (RACF). Participants A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 66 publications
(157 reference statements)
1
7
2
Order By: Relevance
“…Previous studies have reported that being female and widowed are predictors of ADs among older adults [ 14 , 15 , 24 ]; however, no such associations were found in our study. Since other studies have also reported no associations between ADs and gender or marital status [ 17 , 25 , 26 , 27 ], further research on sociodemographic factors is needed.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that being female and widowed are predictors of ADs among older adults [ 14 , 15 , 24 ]; however, no such associations were found in our study. Since other studies have also reported no associations between ADs and gender or marital status [ 17 , 25 , 26 , 27 ], further research on sociodemographic factors is needed.…”
Section: Discussioncontrasting
confidence: 99%
“…Older adults with chronic diseases were more likely to have ADs than those without, which is consistent with the results of previous studies [ 3 , 14 ]. Older patients with comorbidities were more likely to have had prior discussions with their healthcare providers regarding their preference for EOL care [ 14 , 28 ]. Chronic diseases are characterized by a large burden of care because of their prolonged duration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, this is the largest population‐level study identifying the prevalence of ACP documents among acute hospital inpatients. Prevalence statistics are lower compared to similar studies and may be explained by deficiencies in the uptake of ACP documents across both community and acute healthcare settings and exacerbated by low communication of such documents between these sectors 13–15 . Appropriate storage of ACP documents in hospital records is important to ensure that they are readily available to be referred to if a patient loses decision‐making capacity.…”
Section: Discussionmentioning
confidence: 98%
“…Prevalence statistics are lower compared to similar studies and may be explained by deficiencies in the uptake of ACP documents across both community and acute healthcare settings and exacerbated by low communication of such documents between these sectors. [13][14][15] Appropriate storage of ACP documents in hospital records is important to ensure that they are readily available to be referred to if a patient loses decision-making capacity. The applicability of previous prevalence studies is impacted by their focus on smaller population subgroups with an anticipatedly higher prevalence of ACP documents, such as individuals with life-limiting illnesses.…”
Section: Discussionmentioning
confidence: 99%